Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1365-2664.2010.01827.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat degradation and the decline of the threatened mussel Margaritifera margaritifera: influence of turbidity and sedimentation on the mussel and its host

Abstract: Summary1. Habitat degradation is a major reason for species extinctions. For parasite-host interactions, the decline of a parasite may not only be related to the parasite's tolerance to habitat degradation but also indirectly through the host's tolerance to the same disturbance. 2. Our objective was to explore the cause of population declines of the freshwater pearl mussel Margaritifera margaritifera by relating the age distribution, density and growth of the mussels with turbidity, sedimentation rates and den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 44 publications
(72 reference statements)
4
104
0
Order By: Relevance
“…This situation has already been described for many Iberian and other European populations and is the major factor concerning the survival of this species (Álvarez-Claudio et al, 2000;Hastie et al, 2000;Geist, 2010;Österling et al, 2010;Hastie, 2011;Lois et al, 2014). Nevertheless, with the exception of the River Terva, a few juveniles were present.…”
Section: Conservation Statussupporting
confidence: 57%
“…This situation has already been described for many Iberian and other European populations and is the major factor concerning the survival of this species (Álvarez-Claudio et al, 2000;Hastie et al, 2000;Geist, 2010;Österling et al, 2010;Hastie, 2011;Lois et al, 2014). Nevertheless, with the exception of the River Terva, a few juveniles were present.…”
Section: Conservation Statussupporting
confidence: 57%
“…The dredging-induced changes in high turbidity, substrate instability, and sediment grain size might have affected the survival, recruitment, and growth of unionids. Several studies have revealed that increased turbidity can reduce the foraging activity and growth of mussels (Osterling et al, 2007;Bucci et al, 2008;Österling et al, 2010), in which processes several potential mechanisms may be involved. The fraction of fine sediments, which were more abundant at sand extraction sites, was generally responsible for clogging sediments and resulted in low oxygen and high ammonia conditions (Augspurger et al, 2007).…”
Section: > Decadal Changes and Implications For Conservationmentioning
confidence: 99%
“…Sedimentation often has a more local nature compared to increases in turbidity (Thomas et al 2001). Both processes are often addressed in studies describing degradation of marine habitats (Henley et al 2000, Kaiser et al 2006, Airoldi & Beck 2007, Österling et al 2010). …”
Section: Effects Of Enhanced Turbidity On Nature Valuesmentioning
confidence: 99%